WB 2: A high yielding bread wheat variety for irrigated timely sown conditions of North Western Plains Zone of India - Chatrath, Ravish; Tiwari, Vinod; Gupta, Vikas; Kumar, Satish; Singh, Sanjay Kumar; Mishra, Chandra Nath; Venkatesh, Karnam; Saharan, M S; Singh, Gyanendra; Tyagi, B S; Tiwari, Ratan; Sharam, Indu; et al. (Journal of Cereal Research, 2018)
The bread wheat variety WB 2 was released by Central Sub-committee on Crop Standards, Notification and Release of variety, Ministry of Agriculture, Govt of India vide. S.O. 1007(E) dated: 30.03.2017 for cultivation in the North Western Plains Zone of the country. WB 2 has recorded average yield of 51.6q/ha and has shown yield superiority of 2.8% over the best check variety DPW 621-50 (50.2q/ha) over three years of testing under irrigated, timely sown conditions. It has shown resistance to prevalent yellow rust pathotypes 78S84 and 46S119. It is also resistant to virulent pathotype 104-2 of brown rust. It has Lr13+ genes for leaf rust which provides Adult Plant Resistance response and renders it resistant under field conditions. It has good quality characteristics like high grain protein content (12.4%), better grain appearance test weight and better suitability for chapati making. It also has higher sedimentation value reflecting its strong gluten which is indicative of superior bread-making quality. WB 2 also has high grain Zn (42.0ppm) and Fe (40.0ppm) content. Thus, the high yield potential of the variety WB 2 coupled with high grain zinc content makes this variety a suitable choice for the farmers of the NWPZ.